O profissional tradutor e intérprete de libras educacional: desafios da política de formação profissional - Marques, Rogério da Silva (2017)
The current research aims to comprehend the Educational Sign Language Translator's political formation - ESLT, of the teaching state network of the town of Ituiutaba, MG. To reflect about the professional formation of the ESLT, in theoretical and legal field focusing on these professional's trajectory, The research is bibliographical, educational qualitative, documental exploratory. It proposes to identify the ESLT professionals' formation from the documental investigations of the designation's records who worked from 2012 to 2015 in two state networks schools in the town of Ituiutaba. The school 1 was chosen because it was the first regular school that received death students, and consequently the ESLT; and the school 2 was chosen for being the space which the sign language course was taught to the educational professionals of the town's network. It aims to reflect about this professional's formation policy, and it's legal recognition trajectory of the profession and it's professional ethics code. Among the results, it highlights: a) the indispensability to comprehend that the ESLT's formation is not the teaching one, as comprehended by the Minas Gerais state network in it legal orientations, but the Translation and Interpretation in Brazilian Sign Language and Portuguese graduation; b) the wrong understanding about the beginning and further ESLT formation; c) the demand's existence and the access raising to the college graduation in Translation and Interpretation in Brazilian Sign Language and Portuguese in the interior regions; d) There is a need to understand that the ESLT has to be included among the teachers; e) The ESLT's professional constitution, in the studied reality, showed itself in a heterogenous way, sometimes as a teacher, sometimes as specialized support in the communication between death students through the learning process, what gets the Death student's formative process weak, who, according to this research is the main impaired in the misunderstandings of the ESLT's policy formation.